The Effect of Economic Policy Uncertainty in Brazil on Corporate Investment - Batista, Alexandre Teixeira Norberto; Souza, Gustavo Henrique Dias; Bressan, Valéria Gama Fully; Lamounier, Wagner Moura (Advances in Scientific and Applied Accounting, 2024)
Objective: This study investigated the effects of economic policy uncertainty on corporate investments of publicly traded companies listed in Brazil from 2010 to 2020. Uncertainty about economic policy can intensify the value of the option of waiting for new information and cause delays in corporate investments, as suggested by the Real Options Theory. Method: To analyze this relationship, the Systemic Generalized Method of Moments was used, with panel data for a sample of 153 companies, capable of addressing endogeneity problems caused by data of this nature. Results: It was found that increases in economic policy uncertainty cause reductions in the volumes of capital expenditures of companies, with persisting effects in at least four future quarters. Moreover, corporate investments were more responsive to general economic uncertainty, as measured by the Economic Uncertainty Index – Brazil (IIE-Br), than to economic policy uncertainty, as measured by the Economic Policy Uncertainty Index (EPU). Contributions: We confirm that uncertainty in the measured dimensions can delay corporate investments in Brazil. The proposed dynamic model is suitable in predicting firm responses to uncertainty in future periods.This study contributes to a better understanding of the dynamics of corporate investment decisions in Brazil. This information is useful for market analysts in their forecasts, as well as policymakers in developing policies that ensure the balance of such decisions.